Moderation effects of cultural orientations on relationships between interpersonal and intrapersonal interactions in critical thinking disposition of leaners in blended learning environment - Jafarian, Sedigheh (2013)
The increased usage of blended learning mode (combination of traditional classrooms and online learning environments) in distance higher education has led to many challenges to educators, one of which is to ensure critical thinking disposition among students. This study investigates the relationships between quality of interpersonal interaction, intrapersonal interaction, quantity of interpersonal interaction and critical thinking disposition among students in a blended learning environment. Also, it seeks to examine the extent to which the relationships of the above variables are moderated by individualistic-collectivistic cultural orientation at individual level in a blended learning environment in Malaysia. A quantitative correlate ional design was used to collect data using survey instrument. The sample comprised 270 undergraduate students from Pusat Pendidikan Luar (PPL) of Universiti Putra Malaysia. The data were analyzed using Statistical Package for Social Sciences (SPSS) and Analysis of Moment Structure (AMOS) softwares. The findings of this study suggest that quality of interpersonal interaction and intrapersonal interaction significantly influence the critical thinking disposition among students in the blended learning environment. The findings further indicate that characteristics of collectivistic cultural orientation at the individual level significantly moderated the relationship between quality of interpersonal interaction, intrapersonal interaction and critical thinking disposition in the blended learning environment. Therefore it can be concluded that interpersonal and intrapersonal interactions and collectivistic cultural orientation are important factors in increasing learner’s critical thinking disposition in distance higher education context, particularly in the blended learning environment. The results of this study contributed to the advancement of the conceptual framework of inter and intra personal interactions and the influence of cultural differences on critical thinking disposition in a context of blended learning environment in Malaysia. The results of this study are useful for providers and practitioners in the distance higher education context as well as workplace learning contexts in order to design and conduct interactive blended learning programs that can promote students’ critical thinking deposition by considering students’ cultural differences within a society. Further studies were suggested to expand this research to other learning contexts such as other distance learning providers in Malaysia as well as to e-training or blended training in workplace environment.